Biochip array technology and evaluation of serum levels of multiple cytokines and adhesion molecules in patients with newly diagnosed acute myeloid leukemia - Horacek, J.M.; Kupsa, T.; Vasatova, M.; Jebavy, L.; Zak, P. (Experimental Oncology, 2014)
Aim: Evaluation of serum levels of 17 cytokines and 5 adhesion molecules in patients with newly diagnosed acute myeloid leukemia (AML) and in healthy subjects using biochip array technology. Methods: A total of 15 AML patients and 15 healthy subjects (blood donors) were studied. Serum samples were analyzed by biochip based immunoassays on the Evidence Investigator analyzer. This approach allows multi-analytical determination from a single sample. T-tests were used for statistical analysis. Results: In newly diagnosed AML patients, we found significant increase (p < 0.01) in serum VCAM-1, ICAM-1, E-selectin, L-selectin, and significant increase (p < 0.05) in serum IL-6, IL-8. No significant differences were found in the levels of other evaluated cytokines and adhesion molecules. Conclusion: Our results indicate that serum levels of specific cytokines and adhesion molecules (VCAM-1, ICAM-1, E-selectin, L-selectin, IL-6, IL-8) are significantly altered in patients with newly diagnosed AML, showing activity of the disease. Whether these alterations could serve as a prognostic marker for AML is not known. Further studies will be needed to define the potential role of these and additional markers in the risk stratification of AML. Key Words: cytokines, adhesion molecules, biochip array, acute myeloid leukemia.